Peran Kepala Desa sebagai Mediator dalam Mediasi Penyelesaian Sengketa Tanah di Desa Rupe, Kecamatan Langgudu, Kabupaten Bima - Munir; Kasmar; Nurlaili (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the role of the village head as a mediator in resolving land disputes in Rupe Village, Langgudu Subdistrict, Bima Regency. The village head serves not only administratively, but also strategically in mitigating conflict through local wisdom-based mediation. The findings indicate that the village head holds high social legitimacy, effectively facilitating peaceful agreements between disputing parties. The study concludes that mediation success is strongly influenced by public trust in the village head as a neutral figure.